A biomechanical comparison of different tying techniques of a double-stranded looped suture. (2nd December 2019) - Luenam, Suriya; Koonalinthip, Poonsak; Kosiyatrakul, Arkaphat
Purpose: This study aims to assess the biomechanical performance of different tying techniques of a double-stranded looped suture (DSLS). Methods: Loop and knot security of DSLS tying techniques (nice knot (NK), modified nice knot (MNK), double-twist knot (DTK), and double-barrel knot (DBK)) were compared. The square knot of DSLS (SKD) and the square knot of single-stranded suture (SKS) had been used as references. Twenty-four loops of each configuration were created using No. 2 Fiberwire (Arthrex, Naples, Florida, USA) and tested with a material testing machine. Samples were loaded with 10 N preloads for loop security assessment. Knot security was subsequently evaluated. Twelve loops of each knot were loaded to failure. The rest were subjected to cyclic load testing and the elongation at the 50th and 1000th cycles were measured. Knot bulkiness was determined by measuring knot height before testing. Data were compared with analysis of variance and post hoc tests. Statistical significance was p < 0.05. Results: All knots showed no statistically significant difference in displacement with preload. The load-to-failure was highest in NK, followed by MNK, DTK, DBK, SKD, and SKS. The cyclic loading test at the 50th cycle and the 1000th cycle demonstrated that NK has significantly less displacement than the others except MNK. DTK provided a minimal average knot height followed by NK, SKS, DBK, MNK, and SKD. Conclusion: The different tying techniques in DSLS provided the similar loop security but different knot security and knot bulkiness. NK and MNK are biomechanically superior to the other knots, whereas DTK is the least bulky. The findings in the present study may help set the guide for the surgeons to select the tying technique of DSLS to best suit their requirement.